2022
DOI: 10.1038/s41598-022-26689-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel candidate genes and predicted miRNAs in atopic dermatitis patients by bioinformatic methods

Abstract: Atopic dermatitis (AD) is a common, chronic inflammatory dermatosis with relapsing eruptions. Our study used bioinformatics to find novel candidate differentially expressed genes (DEGs) and predicted miRNAs between AD patients and healthy controls. The Mesh term “atopic dermatitis” was retrieved to obtain DEGs in GEO datasets. DEGs between AD patients and healthy controls were analyzed using GEO2R. Overlapping DEGs between different datasets were obtained with use of Draw Venn software. GO and KEGG enrichment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…inflammatory pathways, and keratinization pathways (13)(14)(15). These results provide new directions and strategies for the treatment and prevention of AD and help to improve the quality of life and health of AD patients.…”
Section: Application Of Bioinformatics In Degs Screeningmentioning
confidence: 80%
“…inflammatory pathways, and keratinization pathways (13)(14)(15). These results provide new directions and strategies for the treatment and prevention of AD and help to improve the quality of life and health of AD patients.…”
Section: Application Of Bioinformatics In Degs Screeningmentioning
confidence: 80%
“…Profilaggrin is a predicted target for CAMK2 using phosphorylation-site prediction software (Sandilands et al, 2009) but this has not been explored mechanistically. Chen et al identified CAMK2D as a differentially expressed gene when comparing lesional and non-lesional AE skin to healthy controls using a pooled analysis of microarray datasets (L. H. Chen et al, 2022). However, CAMK2D is poorly enriched in the skin, so further work is necessary to establish if this protein has a role in barrier function or AE.…”
Section: Resultsmentioning
confidence: 99%